Diversity and spatio-temporal distribution of arthropods in the Atlas cedar (Cedrus atlantica Manetti) forest in Belezma National Park (Batna, Algeria) - Salima Zereg; Aicha Mouane; Abdallah Aouadi (Journal of Insect Biodiversity and Systematics)
The study investigated the spatial and seasonal variations in arthropod diversity using different trapping methods within two types of cedar forests (dead and healthy) in Belezma National Park, located in Batna. The field survey was carried out from January 2017 to December 2018, employing three sampling techniques: Barber pots, coloured traps, and suspended traps. A total of 108 species belonging to four classes, 13 orders, and 66 families were recorded. Representing 95.4% of the total species richness, insects were the predominant class, with 46 species. Within this class, Hymenoptera had the highest incidence (46.01%), followed by Diptera (23.6%). The Shannon-Weaver index exceeded 3 across stations, seasons, and sampling methods, indicating high diversity. Additionally, Equitability values surpassed 70% across all observations. PERMANOVA analysis revealed significant differences in composition between the different stations, seasons, and sampling methods. This research highlighted several key factors influencing arthropod diversity, including the condition of the habitat (dead vs. healthy cedar forests), seasonal variations, and the effectiveness of various sampling techniques.